Bālaprauḍha vyākaraṇa karadīpika - Śrīnivāsarāvu, Mailavarapu, 1948- (Śrī Sūryanārāyaṇa Granthamāla, 1976)
Comparative study of the Telugu grammars Bālavyākaraṇamu by Paravastu Chinnaya Suri, 1806-1862, and Prauḍhavyākaraṇamu by Bahujanapalli Sitaramacharyulu, 1827-1891.